2011
DOI: 10.1021/jm200112k
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a 5H-Benzo[4,5]cyclohepta[1,2-b]pyridin-5-one (MK-2461) Inhibitor of c-Met Kinase for the Treatment of Cancer

Abstract: c-Met is a transmembrane tyrosine kinase that mediates activation of several signaling pathways implicated in aggressive cancer phenotypes. In recent years, research into this area has highlighted c-Met as an attractive cancer drug target, triggering a number of approaches to disrupt aberrant c-Met signaling. Screening efforts identified a unique class of 5H-benzo[4,5]cyclohepta[1,2-b]pyridin-5-one kinase inhibitors, exemplified by 1. Subsequent SAR studies led to the development of 81 (MK-2461), a potent inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…16 Consequently, none of the latter reported inhibitors are believed to demonstrate pharmacology primarily related to Mer inhibition. We previously showed that compound 1 is a potent Mer inhibitor (IC 50 1.1 nM) that blocked Mer phosphorylation in cell-based assays, including 697 B-ALL, BT-12 pediatric rhabdoid tumor, NSCLC, and melanoma cell lines.…”
Section: Results and Discussionmentioning
confidence: 99%
“…16 Consequently, none of the latter reported inhibitors are believed to demonstrate pharmacology primarily related to Mer inhibition. We previously showed that compound 1 is a potent Mer inhibitor (IC 50 1.1 nM) that blocked Mer phosphorylation in cell-based assays, including 697 B-ALL, BT-12 pediatric rhabdoid tumor, NSCLC, and melanoma cell lines.…”
Section: Results and Discussionmentioning
confidence: 99%
“…1 Examples of these compounds include loratadine ( 1 , H 1 histamine antagonist), 2 SCH 66336 ( 2 , anti-cancer agent), 3 and MK-2461 ( 3 , anti-cancer agent). 4 The cycloheptabenzopyridine ring system has been previously prepared by intramolecular cyclizations of carboxylic acids, 5 nitriles, 6 alcohols, 7 ketones, 8 and by other routes. 9 For acid-promoted reactions of carboxylic acids, the cyclization requires extreme conditions (i.e., polyphosphoric acid, 200°C).…”
Section: Introductionmentioning
confidence: 99%
“…9k could be furnished smoothly when using the naphthyl substrate 8k. [15] By using 1g as the catalyst, 14 was chlorinated regioselectively to give 15 in 71 %y ield (with 10 %r ecovery of starting material) and the structure of 15 was confirmed unambiguously by an X-ray crystallographic study. [10] Theamide substrates 10 b-d and 12 b,which have either ester or ketone substituents at the meta-position, also gave rise to the C2 chlorinated products 11 b-d and 13 b.The structures of 3fand 13 b were confirmed unambiguously by X-ray crystallographic studies.…”
mentioning
confidence: 96%
“…While secondary ammonium salts have been widely utilized as the organocatalysts in various transformations through the formation of iminium or aminal intermediates,t heir application to site-selective aromatic halogenation remains unknown. [9] With the optimized reaction conditions in hand, we examined the compatibility of different Nsubstituents.I tw as realized that the reaction still could proceed smoothly when replacing the Ns group with Ts and Ms.Arange of carbonyl substituents including Boc, acetyl, and benzoyl could also be tolerated (entries [11][12][13][14][15]. In the absence of catalyst, no reaction was observed after 14 hours (entry 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation